2020
DOI: 10.5539/jas.v12n4p106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zero Tillage and Tillage Practice in Chickpea Production

Abstract: The study was carried out at the field of Regional Pulses Research Station, Madaripur under Bangladesh Agricultural Research Institute (BARI) during Rabi season (winter) to evaluate the effect of different tillage practices on growth, yield attributes, nutrient uptake and yield of chickpea, and to compare between the zero tillage and tillage practice.The experiment was planned with five different tillage practices viz. Zero tillage (T 1 ), Single tillage (T 2 ), Two tillage (T 3 ), Three tillage (T 4 ) and Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
4
2
Order By: Relevance
“…This may be attributed to better seedbed preparation, which might have facilitated better root growth in the no-till plots. These findings could be supported by the previous observations of Quddus et al (2020) in various growth parameters of winter chickpeas with various tillage operations. Among the different lentil varieties studied, the maximum number of nodules plant −1 was found in the short-duration variety L4717 at all the growth stages (Supplemenatry Table S3 and Figures 3-5) in both years.…”
Section: Impact On Growth and Nodulationsupporting
confidence: 89%
See 1 more Smart Citation
“…This may be attributed to better seedbed preparation, which might have facilitated better root growth in the no-till plots. These findings could be supported by the previous observations of Quddus et al (2020) in various growth parameters of winter chickpeas with various tillage operations. Among the different lentil varieties studied, the maximum number of nodules plant −1 was found in the short-duration variety L4717 at all the growth stages (Supplemenatry Table S3 and Figures 3-5) in both years.…”
Section: Impact On Growth and Nodulationsupporting
confidence: 89%
“…Tillage treatments could be arranged as zero tillage (19.30 and 19.95 g) > relay cropping (18.70 and 18.64 g) > conventional tillage (18.00 and 17.85 g) regarding this parameter during 2018-19 and 2019-20. The higher yield attributes in zero tillage plots of lentil crops are also similar to the results of earlier work (Bandyopadhyay et al, 2018;Chauhan et al, 2019;Quddus et al, 2020). The L4717 variety recorded a higher test weight (18.90 and 19.05 g) in both the years of study than the long-duration variety Moitri (18.45 and 18.60 g).…”
Section: Impact On Grain Yieldsupporting
confidence: 89%
“…Zero tillage reduces cost by 3.8 % to 13.7 % and frees up at least 8 days for the growth of succeeding crops. Zero tillage farming is an option for low-income farmers [12].…”
Section: What Is Zero Tillage?mentioning
confidence: 99%
“…Research by Quddus et al [12] showed "variation in growth and yield attributes of chickpea due to different tillage (zero, single, two, three and four times tillage) practices except 100-seed weight. They obtained tallest plant (48.9 cm and 50.1 cm) under zero tillage treatment as compared to the single, two, three and four times tillage treatments, they stated that tallest plant under zero tillage condition observed might be due to availability of optimum soil moisture in soil for available nutrients to plant uptake".…”
Section: Effect On Growth and Yield Attributes Of Chickpeamentioning
confidence: 99%
“…Zero tillage practice could be implemented in the high and medium high land for chickpea cultivation in rice fallows. Low income farmers may practice the zero tillage technology (Quddus et al, 2020).…”
Section: Conservational Agricultural Practicesmentioning
confidence: 99%